2002
DOI: 10.1016/s0014-5793(02)03548-2
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the unliganded Bombyx mori pheromone‐binding protein at physiological pH

Abstract: The nuclear magnetic resonance structure of the unliganded pheromone-binding protein (PBP) from Bombyx mori at pH above 6.5, BmPBP B , consists of seven helices with residues 3^8, 16^22, 29^32, 46^59, 70^79, 84^100, and 107^124, and contains the three disul¢de bridges 19^54, 50^108, and 97117. This polypeptide fold encloses a large hydrophobic cavity, with a su⁄cient volume to accommodate the natural ligand bombykol. The polypeptide folds in free BmPBP B and in crystals of a BmPBP^bombykol complex are nearly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 34 publications
7
120
1
Order By: Relevance
“…6 Inset). Although not entirely surprising, given the size of this peptide (23), this observation indicates that the formation of the C-terminal ␣-helix might be stabilized by interactions of the terminal residues with residues forming the binding cavity (19,22). Except for three acidic residues, the terminal fragment is composed almost entirely of hydrophobic amino acid residues.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…6 Inset). Although not entirely surprising, given the size of this peptide (23), this observation indicates that the formation of the C-terminal ␣-helix might be stabilized by interactions of the terminal residues with residues forming the binding cavity (19,22). Except for three acidic residues, the terminal fragment is composed almost entirely of hydrophobic amino acid residues.…”
Section: Resultsmentioning
confidence: 87%
“…Previously, we suggested that the loss of binding affinity at low pH is due to the occupation of the binding cavity by a C-terminal ␣-helix in Bmor-PBP A (Fig. 3A) (18,19). To test this hypothesis, we expressed a truncated form of BmorPBP B by removing the segment P129-SMDVAVGEILAE-V142 (see Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Conformational heterogeneity has been observed in several other OBPs (14,17,59,60) and is most often associated with residues that regulate access to the ligand binding pocket. However, this heterogeneity is not nearly as extensive as that seen with OBP4 and LUSH.…”
Section: Discussionmentioning
confidence: 99%